2007
DOI: 10.1016/j.febslet.2007.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated and selective recruitment of eIF4E and eIF4G factors for potyvirus infection in Arabidopsis thaliana

Abstract: The translation initiation factors eIF4E and eIF (iso)4E play a key role during virus infection in plants. During mRNA translation, eIF4E provides the cap-binding function and is associated with the protein eIF4G to form the eIF4F complex. Susceptibility analyses of Arabidopsis mutants knocked-out for At-eIF4G genes showed that eIF4G factors are indispensable for potyvirus infection. The colonization pattern by a viral recombinant carrying GFP indicated that eIF4G is involved at a very early infection step. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 30 publications
7
98
0
2
Order By: Relevance
“…S4). However, a redundant role of these two isoforms in regulating the translation of HSA32 could not be excluded, as we did not check the triple KO mutant of eIF4G, eIF (iso)4G1, and eIF(iso)4G2, which could be lethal in Arabidopsis (Nicaise et al, 2007). In addition to translation, HSP101 may retard the degradation of HSA32.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S4). However, a redundant role of these two isoforms in regulating the translation of HSA32 could not be excluded, as we did not check the triple KO mutant of eIF4G, eIF (iso)4G1, and eIF(iso)4G2, which could be lethal in Arabidopsis (Nicaise et al, 2007). In addition to translation, HSP101 may retard the degradation of HSA32.…”
Section: Discussionmentioning
confidence: 99%
“…The double KO mutant hsp101 hsa32-1 was generated by crossing the single mutant lines and isolated from the offspring in the F2 generation. The T-DNA KO mutant of eIF4G and double KO mutants of eIF(iso)4G1 and eIF(iso)4G2 were described in detail previously (Nicaise et al, 2007) and confirmed by PCR analysis with gene-specific primers. EMS-mutagenized M2 seeds (Columbia [Col-0] ecotype) were purchased from Lehle Seeds.…”
Section: Plants Materials and Mutant Screenmentioning
confidence: 99%
“…In A. thaliana, four genes [eIF4E1, eIF4E2, eIF4E3 and eIF(iso)4E] encode proteins of the eIF4E family and three genes [eIF4G, eIF4(iso)G1 and eIF4(iso)G2] encode proteins of the eIF4G family (http://research.cm.utexas.edu/kbrowning/fiat/). The different isoforms appear to carry out complementary biological functions as demonstrated by the lack of specific phenotypes in plants with disrupted eIF4E/4G isomers (Duprat et al, 2002;Nicaise et al, 2007;Sato et al, 2005). An analogous role for PABP is demonstrated here, as individual deletion of constitutive and highly expressing PABP paralogues (i.e.…”
Section: Discussionmentioning
confidence: 75%
“…As seen with TuMV and other potyviruses, the disruption of eukaryotic translation initiation factors such as eIF4E/ eIFiso4E and eIF4G/eIF(iso)4G in A. thaliana leads to potyvirus resistance (Duprat et al, 2002;Lellis et al, 2002;Nicaise et al, 2007) which is indicative of their absolute requirement for virus infection.…”
Section: Isolation Of Viable Single and Double Pab T-dna Insertion Mumentioning
confidence: 99%
See 1 more Smart Citation